(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The mechanical properties of high strength mortars produced with fine waste concrete aggregate (FWCA) and GGBFS were investigated. The natural sand was replaced by FWCA with different levels, namely 0, 25, 50, 75, and 100%. The ordinary Portland cement (OPC) was substituted by GGBFS with 0, 30, and 60% by weight. To satisfy the requirements of high strength, all the mortar mixes were made with a 0.25 w/bratio. The hardened mortars were tested for compressive strength, splitting tension, and fracture parametersat different ages.The experimental findings showed that the mixtures with FWCA showed lower strength, fracture energy and toughness compared to the corresponding reference mixes at a given age and GGBFS content. The 30% replacement of OPC by GGBFS improved the strengths of all mixes at 28 and 90 days. Moreover, the use of 30% GGBFS counterbalanced the strength decrement due to the use of the FWCA such that the mixtures with FWCA and GGBFS showed strengths comparable to or even exceeded the strengths of the mixtures made with natural sand only.